2015
DOI: 10.1007/s11628-015-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-flight attendants’ emotional intelligence, emotional labor, and emotional exhaustion on commitment to customer service

Abstract: Previous studies have shown that the success of airlines depends heavily on the quality of in-flight services provided by flight attendants. The performance of flight attendants is primarily based on their emotional intelligence (EI). Thus, airlines endeavor to recruit flight attendants with high EI and also conduct continuous EI training even after their recruitment. To meet the demand of excellent flight attendants, a number of universities and colleges have established airline service programs. This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 34 publications
(45 reference statements)
0
16
0
3
Order By: Relevance
“…Even though determining the individual traits that influence emotional labor is essential, previous studies have only done so in a limited fashion. Studies of individual traits have focused on specific factors such as psychological resources, emotional intelligence, and emotion [ 5 , 15 , 16 ]. This study introduced service employees’ resilience as the predisposing factor that influences deep acting in the context of emotional labor and expanded the research domain by providing empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though determining the individual traits that influence emotional labor is essential, previous studies have only done so in a limited fashion. Studies of individual traits have focused on specific factors such as psychological resources, emotional intelligence, and emotion [ 5 , 15 , 16 ]. This study introduced service employees’ resilience as the predisposing factor that influences deep acting in the context of emotional labor and expanded the research domain by providing empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have identified resilience as a typical psychological characteristic of individuals recovering from stress [ 14 ], resilience can be expected to play the role of a personal resource that manages job stress and affects the emotional labor of service employees from the JD-R model perspective. Despite the potential positive roles of resilience on emotional labor, previous studies have focused on other limiting factors, such as psychological capital [ 15 ], emotional intelligence [ 16 ], and affectivity [ 5 ], overlooking resilience as a significant factor. Moreover, researchers have not established what role resilience plays in emotional labor.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Ra (2009) explored the negative influence of job stress on service commitment. A research conducted by Jeon (2015) explored the negative relationships between emotional exhaustion and commitment to customer service among flight attendants. Although the relationship between emotional exhaustion and organizational commitment has been tested by many previous studies, the direct relationship between emotional exhaustion and service quality commitment still needs more research to test, especially for middle managers in the hotel industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Little (2007) gelecekteki çalışmalarda, müşteri hizmetleri temsilcileri ve belirli duygusal gösterim kuralları gerektiren diğer işler için duygusal emeğin araştırılmasını ve özellikle duygusal emeğin alt boyutlarından olan derin davranışın incelenmesini önermektedir. Yapılacak araştırmalarda, duygusal emeğin daha yoğun olduğu işlerde özellikle duygusal zekânın rolünün incelenmesi ve farklı ülkelerde daha fazla çalışma yapılması gerektiği tavsiye edilmiştir (Petrides vd., 2016;Jeon, 2016). Türkiye'de duygusal zekâ ve duygusal emeğin birlikte ele alındığı az sayıda çalışmaya rastlanılmaktadır (Adem, 2015;Ayana, 2016;Güler ve Marşap;2019).…”
Section: Introductionunclassified